2014
DOI: 10.1007/s10143-014-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem cavernoma surgery with the support of pre- and postoperative diffusion tensor imaging: initial experiences and clinical course of 23 patients

Abstract: The spatial complexity of highly vulnerable structures makes surgical resection of brainstem cavernomas (BSC) a challenging procedure. Diffusion tensor imaging (DTI) allows for the visualization of white matter tracts and enables a better understanding of the anatomical location of corticospinal and sensory tracts before and after surgery.We investigated the feasibility and clinical usefulness of DTI-based fiber tractography in patients with BSC.Pre- and postoperative DTI visualization of corticospinal and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…DTI studies 11,12,28,31,37,40 in general have qualitatively demonstrated the orientation of the eloquent white matter tracts (deviated and partially interrupted) around the brainstem CMs for planning the surgical trajectory. A recent study 40 using DTI-based tractography retrospectively analyzed the pre-and postoperative visualization of the CST and sensory tracts in 23 cases.…”
Section: Tractography-based Qualitative Data and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…DTI studies 11,12,28,31,37,40 in general have qualitatively demonstrated the orientation of the eloquent white matter tracts (deviated and partially interrupted) around the brainstem CMs for planning the surgical trajectory. A recent study 40 using DTI-based tractography retrospectively analyzed the pre-and postoperative visualization of the CST and sensory tracts in 23 cases.…”
Section: Tractography-based Qualitative Data and Implicationsmentioning
confidence: 99%
“…A recent study 40 using DTI-based tractography retrospectively analyzed the pre-and postoperative visualization of the CST and sensory tracts in 23 cases. The improvement in visualization was associated with the patients' neurological status.…”
Section: Tractography-based Qualitative Data and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…DTT has proven effective for evaluating several brainstem pathologies (12)(13)(14)(15)18). A previous study (13) reported the reliability of DTT in differentiating between diffuse pontine glioma and brainstem demyelinating disease, in which the fiber tracts of the brainstem are displaced by a tumor but are obscured or even transected by demyelinating disease.…”
Section: Discussionmentioning
confidence: 99%